2023
DOI: 10.3389/fnins.2023.1196606
|View full text |Cite
|
Sign up to set email alerts
|

Development of circadian neurovascular function and its implications

Jennifer W. Mitchell,
Martha U. Gillette

Abstract: The neurovascular system forms the interface between the tissue of the central nervous system (CNS) and circulating blood. It plays a critical role in regulating movement of ions, small molecules, and cellular regulators into and out of brain tissue and in sustaining brain health. The neurovascular unit (NVU), the cells that form the structural and functional link between cells of the brain and the vasculature, maintains the blood–brain interface (BBI), controls cerebral blood flow, and surveils for injury. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 220 publications
0
1
0
Order By: Relevance
“…249 Although expression of junctional proteins can exhibit a daily rhythm in the retina, relatively little is known regarding potential changes in these proteins at the BBB. 252 A recent study suggested there is less BBB efflux during the dark phase, when mice are more active, and greater efflux during the light phase. 253 BBB efflux transporter expression and function exhibited a diurnal pattern that was inhibited by endothelial-specific knockdown of Bmal1.…”
Section: Blood-brain Barriermentioning
confidence: 99%
“…249 Although expression of junctional proteins can exhibit a daily rhythm in the retina, relatively little is known regarding potential changes in these proteins at the BBB. 252 A recent study suggested there is less BBB efflux during the dark phase, when mice are more active, and greater efflux during the light phase. 253 BBB efflux transporter expression and function exhibited a diurnal pattern that was inhibited by endothelial-specific knockdown of Bmal1.…”
Section: Blood-brain Barriermentioning
confidence: 99%